Recrystallization of a Ti-45Ni-5Cu cold-worked shape memory alloy characterized by thermoelectric power and electrical properties - Soto Parra, Daniel Enrique; Flores Zúñiga, Horacio; Cuéllar, Enrique López; Ochoa Gamboa, Raul Armando; Ríos Jara, David (2014)
The recrystallization of a cold-worked shape memory alloy (SMA) without R-phase transition, i.e. the Ti-45.0Ni-5.0Cu (% at.), has been studied by thermoelectric power (TEP) technique and electrical resistivity change (Dρ) on several heat treated samples after cold working. This study was also supported by differential scanning calorimetry (DSC), transmission electron microscopy (TEM) and hardness Vickers (HV) measurements. Transformation temperatures show an increase with heat treatment temperature, while hysteresis decreases. Hardness values decrease with aging temperature for the same heat treatment time. No important changes were observed in electrical resistivity with heat treatment temperature, except at 300°C. TEP results show an important increase with heat treatment temperature, and a linear relationship was found between hardness and thermoelectric power. With this correlation between TEP and microhardness it is possible to predict its mechanical response by knowing its TEP, so this correlation could be important for applications.